BENTHIC FORAMINIFER ZONATION IN THE CAMPANIAN-MAASTRICHTIAN OF THE EUROPEAN PALEOBIOGEOGRAPHIC REGION - Beniamovskii V.N.; Kopaevich L.F. (My University, 2001)
Present-day approaches to identification of stage and substage boundaries in the Campanian-Maastrichtian of the European paleobiogeographic region (EPR) are considered. A new zonation of the upper Santonian-Maastrichtian interval that is suggested in this work is based on traceable regularities in evolution of benthic foraminifer genera, which populated different EPR areas. The suggested zonal scheme includes 18 biostratigraphic subdivisions (13 zones and 5 subzones), all having a complex paleontological substantiation. These subdivisions are of different stratigraphic ranges. Those of shorter time spans characterize moments of regressions and incipient transgressions. Two paleobiogeographic provinces, the East and West European, are distinguished in the EPR for the considered interval of time. Despite the close similarity of foraminiferal assemblages, some of their species discriminate one province from another. The West European province was connected with the northwestern Atlantic Ocean better than with the Tethys. The East European province had connections not only with the Tethys, but also with boreal seas of West Siberia via the Middle Uralian, South Uralian, and Turgai straits.
Keywords: Maastrichtian; Campanian; Benthic foraminifer zonation; European Paleobiogeographic Region; West Siberia; Middle Urals; South Urals; Turgai; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Маастрихтский; Мезозой::Меловая::Верхний::Кампанский; Mesozoic::Cretaceous::Upper::Maastrichtian